Preventive effects of Pycnogenol® on cardiovascular risk factors (including endothelial function) and microcirculation in subjects recovering from coronavirus disease 2019 (COVID-19) - Belcaro, Gianni; Cornelli, Umberto; Cesarone, Maria R; Scipione, Claudia; Scipione, Valeria; Hu, Shu; Feragalli, Beatrice; Corsi, Marcello; Cox, David; Cotellese, Roberto; Hosoi, Morio; Burki, Carolina (Minerva medica, 2022)
The aim of this open supplement study was to evaluate the effects of Pycnogenol in comparison with controls on symptoms of post-COVID-19 syndrome and in improving endothelial function, microcirculation, inflammatory markers and oxidative stress over 3 months in symptomatic subjects recovering from COVID-19. Sixty subjects recovering from symptomatic COVID-19 were included. One group of 30 followed a standard recovery management while 30 comparable subjects received a supplement of 150 mg Pycnogenol daily (in 3 doses of 50 mg) in addition to standard management. Two groups of selected subjects were comparable at baseline. The groups progressively improved both with the SM (standard management) and with the SM in combination with the supplement. Patients, supplemented with Pycnogenol showed significantly better improvement compared to the control group patients. No side effects from the supplementation were observed; tolerability was optimal. The progressive evolution over time was visible in all target measurements. Physiological tests: endothelial function, low in all subjects at inclusion was assessed by flow mediated dilation (FMD) and finger reactive hyperemia in the microcirculation (laser Doppler measurements) after the release of an occluding suprasystolic cuff. It was significantly improved in the Pycnogenol group after one month and after 3 months (P<0.05 vs. controls). The rate of ankle swelling (RAS) by strain gauge decreased significantly in the supplemented group (P<0.05) in comparison with controls showing an improvement of the capillary filtration rate. At inclusion, the kidney cortical flow velocity indicated a decrease in perfusion (lower systolic and diastolic flow velocity) in all patients. Kidney cortical flow velocity increased significantly with the supplement (P<0.05) in comparison with controls with improvement in systolic velocity and in diastolic component. High sensitivity CRP (hs-CRP) and Il-6 plasma levels decreased progressively over 3 months with a significant more pronounced decrease in the supplement group (P<0.05). The number of patients with normal plasma IL-6 levels at the end of the study was higher (P<0.05) with the supplement. ESR followed the same pattern with a progressive and a more significant decrease in the supplemented subjects (P<0.02). Oxidative stress decreased significantly in the supplemented group (P<0.05) compared with the control group. Systolic blood pressure was significantly lower in the supplemented group (P<0.05) at the end of the study. Finally, the scores of Quality-of-life, mood and fatigue questionnaire and the Karnofsky Scale Performance Index significantly improved in the supplement group (P<0.05) compared to controls after 1 and 3 months. All other blood parameters (including platelets and clotting factors) were within normal values at the end of the study. In conclusion, Pycnogenol may offer a significant option for managing some of the signs and symptoms associated with post-COVID-19 syndrome. This pilot evaluation offers some potential rationale for the use of Pycnogenol in this condition that will have significant importance in the coming years.